Oxidized [1-14 c] linoleic acid and hydrogen peroxide tone might promote anti-atherogenic action and prevent metabolic diseases - PRATIBHA KAMBLE (International Journal of Pharma and Bio Sciences, 2017)
Oxidized low density lipoprotein (Ox-LDL) and its various forms are responsible for development of proatherogenic action in in vitro cell culture system. Reactive oxygen species (ROS) can produce detrimental effects that include atherosclerosis. However, mild oxidized products could also impose antiatherogenic action. Present study suggests that HepG2 cells treated with [1-14C] Linoleic acid formed oxidized linoleic acid (13-hydroperoxy-9,11-octadecadienoic acid) [13-HPODE] and hydrogen peroxide [H2O2]. In addition to that cells exposed to oxidized [1-14C] HPODE showed peroxisomal degradation of oxidized [1-14C] HPODE to H2O2 which might be a lipoxygenase enzymatic reaction. Azelaic acid which is lipid peroxidation-derived lipophilic dicarboxylic acid is also formed during the reaction. The generation of this compound can induce anti-atherosclerotic effect. Similarly, in absence of HepG2 cells [1-14C] linoleic acid and [1-14C] HPODE independently formed least oxidation. Ox-LDL treatment to HepG2 cells at 0-4 h showed increase in H2O2 generation. Ox-LDL alone showed rise in lipid peroxide and H2O2 content at 1h. A cellular change was also noticeable effect of Ox-LDL and HPODE treatment.